2017
DOI: 10.1177/0886260517739285
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Responding to Survivors of Sexual Assault: A Qualitative Study of Survivors and Support Providers

Abstract: Empirical research has repeatedly examined the social reactions survivors receive from informal and formal support providers. This research has also provided an understanding of social reactions survivors perceive as helpful and hurtful. Advocacy agencies provide supplemental information instructing support providers how to respond to survivors in a positive way. However, these sources-to our knowledge-have not specifically asked survivors how they want to be responded to when disclosing assault and what they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 14 publications
0
44
0
1
Order By: Relevance
“…Unexpected negative reactions, including blame, judgment, disbelief, and lack of empathy may negatively in uence well-being and recovery (33,34). Negative social reactions to sexual assault disclosures may amplify feelings of powerlessness, grief, loss, and disenfranchisement (7), shame (35,36), increased severity and duration of PTSD (37) and other mental health concerns (38). When the sense of self (e.g., self-worth) is negative, there are often greater risk-taking behaviours as survivors may not feel that they are worthy of protecting or deserving of safety and wellness (37).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unexpected negative reactions, including blame, judgment, disbelief, and lack of empathy may negatively in uence well-being and recovery (33,34). Negative social reactions to sexual assault disclosures may amplify feelings of powerlessness, grief, loss, and disenfranchisement (7), shame (35,36), increased severity and duration of PTSD (37) and other mental health concerns (38). When the sense of self (e.g., self-worth) is negative, there are often greater risk-taking behaviours as survivors may not feel that they are worthy of protecting or deserving of safety and wellness (37).…”
Section: Discussionmentioning
confidence: 99%
“…Their voices (e.g., research themes) need to be disseminated to provide a better understanding of women's experiences, which may lead to increased sexual assault reporting and an improved response from law enforcement. Education regarding women's experiences and how to respond positively to survivors is required for community service providers, police, and healthcare professionals who receive sexual assault reports (21,38,48). Sensitivity training for police o cers that is inclusive of women's voices and experiences may also serve to reduce bias, and improve belief of survivors.…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Advocacy services also can improve victims’ well-being in other ways besides providing support during criminal justice processes. Krikner and colleagues (2017) found that survivors thought it was important to share their experience with someone but highlighted the importance of doing so with an individual who had specialized training in sexual assault issues, such as an advocate or SANE. In addition, Campbell (2006) examined the ways victim services led to significant improvement in victims’ emotional well-being.…”
Section: Community Responses To Sexual Assault: a Survivor’s Pathmentioning
confidence: 99%